An investigation on the deterioration of physical and mechanical properties of granite after cyclic thermal shock. (December 2021) - Pai, Ning; Feng, Ju; Haijian, Su; Zequan, He; Meng, Xiao; Yazhen, Zhang; Cheng, Zhou; Dong, Wang
Highlights: Cyclic thermal shock effect on physical, mechanical and AE characteristics of granite was investigated. Degradation mechanism of granite after thermal shock is analyzed by thermal cracks development. The temperature gradient and thermal stress state of granite during thermal shock were analyzed. The maximum tensile thermal stress of granite during thermal shock was up to 9.18 MPa. Abstract: As one of the main thermal storage medium of hot dry rock geothermal resources, granite is often subject to frequent thermal shock during the geothermal exploitation. Grasping the response regularity of granite to thermal shock is of great significance to the construction and long-term reliability evaluation of enhanced geothermal system (EGS). This paper investigated the physical and mechanical properties of granite after 0∼20 thermal shocks, and discussed its internal deterioration mechanism. Combined with ANSYS numerical simulation analysis, the mechanical formation mechanism of thermal cracks that lead to the deterioration of physical and mechanical properties of granite was analyzed. The results show that the first thermal shock tends to cause the severest deterioration to both physical and mechanical properties of granite. But when the number of thermal shocks exceeds 10, the deterioration slows down. The increase in contact thermal resistance between mineral particles after cyclic thermal shock results in a decrease in the thermal conductivity of granite. The enhancement of local stress concentration effect and the increase of local bearing capacity difference of granite after cyclic thermal shock result in the decrease of peak strength and the enhancement of ductility characteristics of granite. Due to the existence of thermal cracks, the granite after cyclic thermal shock has one more path to release the energy stored during the loading process than the natural granite. Therefore, the maximum counts at the beginning of crack propagation and the entire crack propagation stage are smaller than that of the natural granite. During the thermal shock, the huge instantaneous temperature difference between the interior and exterior of granite leads to the formation of thermal stress, which increases rapidly and then disappears gradually. As a result, the interior of granite mainly bears the effect of the vertical compressive thermal stress up to 7.59 MPa, while the exterior of granite mainly bears the effect of vertical tensile thermal stress up to 9.18 MPa. The propagation of some pre-existing micro cracks with proper orientation in the interior of granite and the initiation and propagation of secondary thermal cracks on granite surface are identified as two main causes to the deterioration of the physical and mechanical properties of granite after cyclic thermal shock.